Nuevo registro al norte de Colombia de la serpiente alacranera, Stenorrhina degenhardtii Berthold 1846 (Squamata: Colubridae), con comentarios sobre su comportamiento defensivo. - Acuña-Vargas, Julio Cesar; Yepes-Pérez, Yoelis; Jotty A., Karick (Instituto de Ecología, A.C., 2018)
A confirmed record of the Scorpion-eating Snake, Stenorrhina degenhardtii (Berthold 1846), is provided for the valleys between the Sierra Nevada of Santa Marta and Serrania de Perija in the municipality of El Molino, department of La Guajira. This record extends the geographic distribution of this species in the Caribbean Region, Northeast of Colombia. The information presented herein contributes to the knowledge of S. degenhardtii natural history and reptile diversity in the department of La Guajira, Colombia.